DOES THE WRITER OF ENGLISH TEXTBOOK INTEGRATE NORMS IN READING PASSAGES HE/SHE WROTE? - Achmad Hilal Madjdi; Atik Rokhayani (Universitas Muria Kudus, 2018)
A serious challenge which is faced by teachers is educating character and bringing norms being practiced by the society into the classrooom, and English teacher is no exception. The challenge makes IndonesianEducation is very dynamic as everything dealing with normsis always thethe concern and developed by scholars, parents as well as the government. Some scholars propose to foster English teachers as models of practicing norms, while some others think to integrate norms into teaching materials. The second thought invites curriousity on how the writer of English textbook supports the recent concern on norms, and the research on it becomes very important to do. Therefore the research dealing with several reading passages in the English Textbook was done. The design was descriptive qualitative which aimed at investigating whether the writer of English textbook integrates norms in reading passages he/ she wrote. The data was norms, while the data sources were reading passages in the 2015-English Textbook developed by The Ministry of Education and Culture. The result describes that norms of trust, discipline, respect to others and self-confidence were found in reading passages. It can be then concluded that the writer of English textbook integratesnorms in the text he/ she writes. The results of the research implies not only the seriousness of scholars, parents and government in fostering character education, but also the support and care of textbook writer in succeeding the education.It is therefore suggested to teachers, scholars as well as book writer to always concern with the society’s need in developing education, especially in sharing the existed and practiced norms.